Perceptibility and Acceptability of Surface Gloss Variation Under Different Illuminants - Rocha, R. S. [UNESP]; Carvalho, V. G. de [UNESP]; Galvao, M. N. C. [UNESP]; Souza, M. Y. de [UNESP]; Caneppele, T. M. F. [UNESP]; Bresciani, E. [UNESP] (Operative Dentistry Inc, 2021)
Objective: The purpose of this study was to evaluate the influence of different illuminants on the perceptibility and acceptability of surface gloss variations and to determine limiting values. Methods: Eight composite resin specimens and one human tooth specimen were polished to obtain composite resin specimens with different gloss units (GU) of 10, 20, 30, 40, 50, 60, 70, and 80 and a human tooth specimen of 80 GU. Sixty observers compared the surface gloss of the specimens in a light booth. For perceptibility testing, the specimens were randomly positioned two at a time. The acceptability of the gloss variation was determined by comparing the composite resin specimens with the tooth specimen. The observers answered specific questions to determine the level and perceptibility and acceptability limits of gloss variations. All analysis was done with two illuminants (D65 and fluorescent light) used randomly. Data were submitted to a nonlinear probit model and nonlinear probit regression estimation (alpha=0.05). Results: Significant differences in illuminants were observed for perceptibility (p<0.001) and acceptability (p=0.045). The perceptibility limit for D65 was 7.0 GU and 6.8 GU for fluorescent illuminant. The acceptability limit for D65 was 34.2 GU and 37.1 GU for fluorescent illuminant. Conclusions: More accurate perceptibility and acceptability judgments of the surface gloss of composite resin were made when the specimens were illuminated with D65 light.